Charter and Revised Ordinances of the City of San Jose 91 (1882) - (:unkn) unknown (My University, 1882)
§§ 2-4: Prohibited the use or possession of any slung-shot, rubber sling, or other instrument or device by which missiles are hurled or projected. Also prohibited the wear or carry of any slung-shot, knuckles, or other similar instruments. Also prohibited the sale, or transfer to any minor under the age of twelve, any revolver, pistol, or other means to shoot bullets or missiles. Only public officers may wear or carry any pistol, dirk, or other dangerous weapon.
Keywords: CARRY - NON-GUN ARMS; TRANSFER - MINORS